UPAYA MENINGKATKAN HASIL BELAJAR TEMA PERSATUAN DALAM PERBEDAAN MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES SISWA KELAS VI SD NEGERI 01 TANJUANG GADANG KECAMATAN LAREH SAGO HALABAN SEMESTER 1 TAHUN PELAJARAN 2019/2020 - Yusniar Yusniar (Ensiklopedia of Journal, 2022)
Abstract: Based on the results of temporary observations, it can be seen in the teaching and learning process in the classroom the following things:1. Low student learning outcomes, 2. Lack of student activity in following the teaching and learning process, 3. There is no fun learning, 4. There is no creative learning. This study was conducted with the aim of describing Efforts to Improve Learning Outcomes with the Theme of Unity in Difference Using Learning Models Examples Non Examples for Class VI students of SD Negeri 01 Tanjuang Gadang, Lareh Sago Halaban District, Semester 1 of the 2019/2020 Academic Year. Classroom Action Research (CAR) is a form of reflective study by the perpetrators of the actions taken to improve the rational ability of the actions they take, as well as to improve the real conditions in which the practice of implementing the learning is carried out in the classroom. In this classroom action research (CAR), the research model developed by Kemmis and Taggart uses a spiral system cycle, each cycle consists of 4 components, namely: 1) planning; 2) action; 3) observation and 4) reflection. Student learning outcomes, the researchers held a test for each cycle. The results of the second cycle test were compared with the KKM that had been set at SD Negeri 01 Tanjuang Gadang, Lareh Sago Halaban District, Semester 1 of the 2019/2020 Academic Year, which was 75 for individual completeness. Based on the results of the test above, it can be seen that in the first cycle of 16/55% of students, 13 students or 45% completed, and in the second cycle 26/89 students who completed learning. This proves that student learning outcomes in the first cycle to the second cycle are 36%.Keywords: Learning Outcomes, Examples Non Examples.